Induction of Apoptotic Cell Death by Oral Streptococci in Human Periodontal Ligament Cells - Park, Ok-Jin; Kim, A Reum; So, Yoon Ju; Im, Jintaek; Ji, Hyun Jung; Ahn, Ki Bum; Seo, Ho Seong; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Microbiology, 2021)
Initiation and progression of oral infectious diseases are associated with streptococcal species. Bacterial infection induces inflammatory responses together with reactive oxygen species (ROS), often causing cell death and tissue damage in the host. In the present study, we investigated the effects of oral streptococci on cytotoxicity and ROS production in human periodontal ligament (PDL) cells. Streptococcus gordonii showed cell cytotoxicity in a dose- and time-dependent manner. The cytotoxicity might be due to apoptosis since S. gordonii increased annexin V-positive cells, and the cytotoxicity was reduced by an apoptosis inhibitor, Z-VAD-FMK. Other oral streptococci such as Streptococcus mitis, Streptococcus sanguinis, and Streptococcus sobrinus also induced apoptosis, whereas Streptococcus mutans did not. All streptococci tested except S. mutans triggered ROS production in human PDL cells. Interestingly, however, streptococci-induced apoptosis appears to be ROS-independent, as apoptosis induced by S. gordonii was not recovered by the ROS inhibitors resveratrol or n-acetylcysteine. Instead, H2O2 appears to be important for the cytotoxic effects of streptococci since most oral streptococci except S. mutans generate H2O2, and the cytotoxicity was dramatically reduced by catalase. Furthermore, streptococcal lipoproteins are involved in cytotoxicity, as we observed that cytotoxicity induced by the lipoprotein-deficient S. gordonii mutant was less potent than that by the wild-type and was attenuated by anti-TLR2-neutralizing antibody. Indeed, lipoproteins purified from S. gordonii alone were sufficient to induce cytotoxicity. Notably, S. gordonii lipoproteins did not induce H2O2 or ROS but cooperatively induced cell death when co-treated with H2O2. Taken together, these results suggest that most oral streptococci except S. mutans efficiently induce damage to human PDL cells by apoptotic cell death with bacterial H2O2 and lipoproteins, which might contribute to the progression of oral infectious diseases such as apical periodontitis.